2021
DOI: 10.3390/pharmaceutics13101592
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial Cellulose as a Potential Bio-Scaffold for Effective Re-Epithelialization Therapy

Abstract: Currently, there are several therapeutic approaches available for wound injury management. However, a better understanding of the underlying mechanisms of how biomaterials affect cell behavior is needed to develop potential repair strategies. Bacterial cellulose (BC) is a bacteria-produced biopolymer with several advantageous qualities for skin tissue engineering. The aim here was to investigate BC-based scaffold on epithelial regeneration and wound healing by examining its effects on the expression of scaveng… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 72 publications
0
19
0
1
Order By: Relevance
“…iNOS and ARG are induced by M1 and M2 macrophages respectively. 61 M1 macrophages with pro-inflammatory properties induce osteoclastogenesis to enhance bone resorption at an early stage. M2 macrophages with anti-inflammatory properties support tissue repair at a late stage.…”
Section: Resultsmentioning
confidence: 99%
“…iNOS and ARG are induced by M1 and M2 macrophages respectively. 61 M1 macrophages with pro-inflammatory properties induce osteoclastogenesis to enhance bone resorption at an early stage. M2 macrophages with anti-inflammatory properties support tissue repair at a late stage.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, the surface characteristics play a crucial role in determining the performance of a biomaterial [ 46 ]. Surface properties such as topography, wettability, surface charge, and chemistry can directly influence the cell-surface interactions through the transduction of biomechanical stimuli into chemical stimuli, resulting in the activation of different signaling pathways which guide different cellular responses such as the integration of the biomaterial with the host tissue, appropriate immune responses, and infection prevention [ 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 ]. Better surface characteristics gives the possibility of improved interaction with living cells which would then support migration of epithelial cells and fibroblasts to help in accelerated replacement of the lost or damaged tissues resulting in protection of the wound from infection, reducing pain, and lowering health care expenses.…”
Section: Functionalization Of Bc Hydrogelsmentioning
confidence: 99%
“…For instance, bacterial cellulose (BC) has attracted scientific interest in developing innovative scaffolds. Cherng et al [ 125 ] have evaluated the potential of BC-based scaffolds of epithelial regeneration and wound healing in vitro and in vivo. The authors reported excellent biocompatibility in vitro, as the material was able to maintain the stemness function of cells and promote keratinocyte differentiation.…”
Section: Biomaterials Scaffoldsmentioning
confidence: 99%
“… Classification and examples of polymers used for fabricating biomaterial scaffolds. Created based on information from [ 115 , 118 , 120 , 121 , 122 , 123 , 124 , 125 , 126 ]. Abbreviations: PCL—poly (ε-caprolactone), PLA—polylactic acid, PLGA—poly(lactic-co-glycolic acid), PAM—polyacrylamide, PHB—poly-3-hydroxybutyrate, PUR—polyurethane.…”
Section: Figurementioning
confidence: 99%